Remission from antipsychotic treatment in first episode psychosis related to longitudinal changes in brain glutamate - Merritt, Kate (NPJ Schizophr, 2019)
Neuroimaging studies in schizophrenia have linked elevated glutamate metabolite levels to non-remission following antipsychotic treatment, and also indicate that antipsychotics can reduce glutamate metabolite levels. However, the relationship between symptomatic reduction and change in glutamate during initial antipsychotic treatment is unclear. Here we report proton magnetic resonance spectroscopy (1H-MRS) measurements of Glx and glutamate in the anterior cingulate cortex (ACC) and thalamus in patients with first episode psychosis (n = 23) at clinical presentation, and after 6 weeks and 9 months of treatment with antipsychotic medication. At 9 months, patients were classified into Remission (n = 12) and Non-Remission (n = 11) subgroups. Healthy volunteers (n = 15) were scanned at the same three time-points. In the thalamus, Glx varied over time according to remission status (P = 0.020). This reflected an increase in Glx between 6 weeks and 9 months in the Non-Remission subgroup that was not evident in the Remission subgroup (P = 0.031). In addition, the change in Glx in the thalamus over the 9 months of treatment was positively correlated with the change in the severity of Positive and Negative Syndrome Scale (PANSS) positive, total and general symptoms (P<0.05). There were no significant effects of group or time on glutamate metabolites in the ACC, and no differences between either patient subgroup and healthy volunteers. These data suggest that the nature of the response to antipsychotic medication may be related to the pattern of changes in glutamatergic metabolite levels over the course of treatment. Specifically, longitudinal reductions in thalamic Glx levels following antipsychotic treatment are associated with symptomatic improvement.